A portfolio theory based optimization model for steam coal purchasing strategy: A case study of Taiwan Power Company. Issue 2 (June 2016) - Huang, Yun-Hsun; Wu, Jung-Hua
Abstract: The price of coal has fluctuated dramatically in recent years, resulting in the uncertainty of the coal purchasing decision. As a result, reducing costs and managing risk are issues of tremendous importance to power companies. This study developed a model for the purchase of steam coal, taking into account the risks associated with fluctuations in the price of coal. The proposed model combines portfolio theory with conventional mathematical programming. The model also considers limitations in the demand for coal, the upper limit of imports from specific sources, power plant operational requirements, and environmental constraints. Scenario analysis was conducted to simulate changing patterns in the factors influencing the purchase of coal. Simulation results reveal that incorporating the dimension of price risk within a conventional coal purchasing model shifts purchasing decisions toward contracts with long-term suppliers, thereby reducing susceptibility to fluctuations in coal prices. However, the case study in this paper is a state-owned company; therefore, its coal purchasing portfolio lacks flexibility due to complex prequalification requirements. Related restrictions (e.g. strict qualification requirements) must be relaxed to increase the number of available sources and take advantage of the benefits provided by the proposed model. Highlights: No study has focused on coal purchasing strategies incorporating price risk. This study fills this gap in the literature. Incorporating price risk creates a preference for coal from long-term contracts. This study demonstrates the applicability of portfolio theory in coal purchasing.